SYNERGY OF BP4 WITH SUB-DISTRICT OF KUA IN REALIZING FAMILY RESILIENCE IN SERANG CITY, BANTEN - Muhammad Ishom; Ahmad Jamaludin Jambunanda (Syakhsia Jurnal Hukum Perdata Islam, 2023)
This study aims to analyze the synergy factor of BP4 with KUA in an effort to realize family resilience in Serang City, Banten. BP4 ideally becomes an institution that functions to realize family resilience by strengthening the values of harmony in the family and preventing the possibility of collapse of household bonds caused by conflicts between husband and wife. Sociological legal research using field data achieved the results of the analysis that BP4 in Serang City experienced dysfunction for several reasons, including: (1) there is no clarity on the orientation of BP4 after becoming an independent institution; and (2) the lack of operational funds of the institution. To cover this problem, BP4 needs to synergize with sub-district of KUA according to their respective duties and authorities.